Assessing The Suitability of a Single Brand of MSMES In the Hospitality Sector to Boost Sustainable Development: The Case of Mauritius - Pompeia, Michael Louis Fabien (Emerald, 2021)
Abstract/ Purpose: The purpose of this paper is to assess the suitability of a single brand for micro, small and medium enterprises (MSMEs) in the hospitality sector to boost sustainable development in Mauritius.